Dynamics of anterior pituitary immunoreactive gonadotrophs in moulted hens supplemented with protein, symbiotic and probiotics. Issue 3 (3rd September 2015) - Anwar, H.; Rahman, Z. U.
Summary: The present work delineates redistribution patterns of the hormone‐producing cells of the anterior pituitary, after the phase of moulting. Two hundred single comb White Leghorn hens at the end of their first production cycle (Age = 70 week) were purchased from the commercial poultry farm and were induced to moult by high‐dietary zinc (3 g/kg feed/day) after 1 week of acclimatization, at the experimental research station, Department of Physiology and Pharmacology, University of Agriculture, Faisalabad. The moulted birds were equally ( n  = 50) and randomly allocated to their respective groups as G1 (control; CP (Crude protein) 16%, no supplement), G2 (CP18%, no other supplement), G3 (CP16%, symbiotic at does rate of 85 mg/l in drinking water daily) and G4 (CP16%, probiotic at dose rate of 85 mg/l in drinking water daily). Ten birds were slaughtered in each group at 5% and at peak of post‐moult production stage to collect their pituitary glands. An earlier post‐moult production recovery, sustained and lengthier production span was seen in the G2 as compared to all other groups. The lowest production and an earlier production decline were seen in G1. The cell diameter and area of follicle‐stimulating hormone (FSH) and luteinizing hormone (LH) gonadotroph increased (p ≤ 0.01) in G2 and G3 as compared to G1. The FSH gonadotroph nucleus diameter and area did increase (p ≤ 0.01) in G2 and G3, while LH gonadotroph nucleus diameter and area decreased (p ≤ 0.01) in G2 and G3 as compared to G1. The increased FSH and LH gonadotroph diameter in protein and symbiotic supplemented birds is accountable for the increased egg production in these groups.